2016
DOI: 10.1007/s00228-016-2029-x
|View full text |Cite
|
Sign up to set email alerts
|

CES1P1 variant −816A>C is not associated with hepatic carboxylesterase 1 expression and activity or antihypertensive effect of trandolapril

Abstract: Purpose The majority of angiotensin-converting enzyme inhibitors (ACEIs) are synthesized as ester prodrugs that must be converted to their active forms in vivo in order to exert therapeutic effects. Hepatic carboxylesterase 1 (CES1) is the primary enzyme responsible for the bioactivation of ACEI prodrugs in humans. The genetic variant −816A>C (rs3785161) is a common variant located in the promoter region of the CES1P1 gene. Previous studies report conflicting results with regard to the association of this vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…As the predominant hepatic hydrolase, CES1 plays a critical role in the activation/deactivation of various medications. Importantly, previous studies have shown hepatic CES1 expression and activity to vary among individuals by 11.3‐fold and 47.8‐fold, respectively. Additionally, significant interindividual variability has been consistently reported in responses to CES1 substrate medications, which is in part associated with CES1 genetic polymorphisms .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As the predominant hepatic hydrolase, CES1 plays a critical role in the activation/deactivation of various medications. Importantly, previous studies have shown hepatic CES1 expression and activity to vary among individuals by 11.3‐fold and 47.8‐fold, respectively. Additionally, significant interindividual variability has been consistently reported in responses to CES1 substrate medications, which is in part associated with CES1 genetic polymorphisms .…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, we recently conducted a comprehensive functional study of CES1 nonsynonymous variants and revealed a few CES1 SNPs which impaired CES1 activity in the hydrolysis of enalapril, clopidogrel, and sacubitril; these include L40Ter (rs151291296), A158V (rs202121317), R199H (rs2307243), E220G (rs200707504), and T290M (rs202001817) . Aside from nonsynonymous variants, two SNPs ‐816A>C (rs3785161) and ‐75T>G (rs3815583), located in the promoter regions of CES1P1 and CES1 , respectively, have been reported to be associated with responses to CES1 substrates, such as imidapril, clopidogrel, and methylphenidate, although not all studies have supported this association . Taken together, these findings have established an important role for CES1 genetic polymorphisms in regulating CES1 function; however, it is worth noting that a substantial portion of CES1 variability remains unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the G143E, other CES1 variations such as the −816A>C (rs3785161) and functional CES1 gene copy numbers were suggested by several clinical studies to be associated with the metabolism of some CES1 substrate drugs [30-32]. However, our recent in vitro CES1 pharmacogenetic studies utilizing individual human livers demonstrated that neither CES1 expression nor activity was affected by the −816AA>C and functional CES1 gene copy variants [22, 33]. Pare and associates conducted a genome-wide association study in RE-LY study participants, and reported that the CES1 SNPs rs2244613 and rs8192935 were associated with lower plasma concentrations of DAB, and the rs2244613 was also associated with a lower risk of bleeding [4].…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al (2014) also performed a retrospective pharmacogenetic analysis of the INternational VErapamil SR Trandolapril study (n 5 486) and did not find an association between -816A.C and the blood pressure-lowering effect of trandolapril. The follow-up in vitro study also showed -816A.C genotype was not significantly associated with CES1 protein expression and trandolapril activation in human liver samples (n 5 100) (Zhu et al, 2016). Other researchers also noted that the CES1P1 VAR gene, which contains -816A.C, is considered functionally insignificant because of its low transcription efficiency (Tanimoto et al, 2007;Hosokawa et al, 2008).…”
Section: Downloaded Frommentioning
confidence: 92%